Peran Media Sosial Terhadap Pembentukan Identitas Nasional Mahasiswa di Era Digital - Mahendra, Sandifa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
has become the main platform for social interaction and information dissemination. The purpose of this study is to evaluate how social media contributes to the formation of students' national identities, taking into account technological, social, and cultural elements. The positive and negative impacts of social media on the strengthening of national values are researched with a qualitative approach and literature study methodology. Studies show that social media can help build a national identity by spreading positive content such as the country's history, culture, and achievements. However, on the other hand, there are challenges such as the spread of misinformation, the influence of foreign cultures, and the polarization of opinions that can threaten the unity of national identity. Therefore, collaborative efforts are needed between educational institutions, the government, and the community to optimize the role of social media as an educational medium and strengthen students' national identity in the digital era.